Genetic Variation in Remnant Populations of Dalbergia nigra (Papilionoideae), an Endangered Tree from the Brazilian Atlantic Forest - RIBEIRO, RENATA ACÁCIO (Ann Bot, 2005)
• Background and Aims Dalbergia nigra, known as Brazilian rosewood, is an endangered tree species restricted to the Brazilian Atlantic Forest and has been intensively logged for five centuries due to its high-quality wood. The objective of the present study was to assess the genetic variation and structure in adults and saplings of the species from a large reserve of the Atlantic Forest, the Rio Doce State Park, and from two small surrounding fragments, one better preserved and another with a high degree of anthropogenic disturbance. • Methods Analyses of genetic variation and structure were conducted by studying allozyme markers. Seven putative enzymatic loci were resolved, five of them being polymorphic. • Key Results The mean numbers of alleles per locus (A) were 1·93 and 1·73, while the percentages of polymorphic loci (P) were 93 and 73 % for adults and saplings, respectively. Saplings from the fragment with high anthropogenic disturbance exhibited the lowest values of A and P. The fragment that constitutes a conservation area exhibited genetic variation similar to the population from the large reserve. The observed (H(o)) and expected (H(e)) heterozygosities were not significantly different among the three populations. Only sapling populations showed F(ST) values (divergence among populations) significantly different from zero over all studied loci. The fragment with high anthropogenic disturbance exhibited considerable genetic divergence in relation to the above-cited populations. • Conclusions The evaluated populations displayed mean levels of genetic variation intermediate to those expected for narrow and widespread species. The results suggest that fragments with similar area and geographical distance from a large protected reserve can exhibit different levels of genetic variation, depending on the degree of anthropogenic disturbance. The considerable genetic variation in the protected fragment points to the importance of adequate conservation of small fragments for the preservation of genetic variation in D. nigra.